2019
DOI: 10.1111/ipd.12479
|View full text |Cite
|
Sign up to set email alerts
|

Does dental trauma influence the social judgment and motivation to seek dental treatment by children and adolescents? Development, validation, and application of an instrument for the evaluation of traumatic dental injuries and their consequences

Abstract: Background One's smile clearly plays a significant role in the perception and judgment that others have of one's appearance and personality. Aim We sought to develop and validate a questionnaire related to the social judgment of children and adolescents and to evaluate, through its application, the perceptions and judgment of children and adolescents regarding their view of different traumatic dental injuries and their consequences (TDIs‐Cs) as well as the motivation to seek dental treatment. Design The aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…Previous studies have reported that TDI occurrence, especially in anterior teeth, has consequences that may impact the aesthetics, 32 quality of life, 33,34 psychosocial behaviours 32 and social reception 8 of children and/or adolescents, and the treatment of TDI is necessary to minimize some of these negative impacts 35 . Once a tooth has been traumatized, local sequelae may occur immediately or over the months or years thereafter, 6,36 leading to the requirement of years of follow‐up after a dental trauma treatment, resulting in further direct and indirect costs 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that TDI occurrence, especially in anterior teeth, has consequences that may impact the aesthetics, 32 quality of life, 33,34 psychosocial behaviours 32 and social reception 8 of children and/or adolescents, and the treatment of TDI is necessary to minimize some of these negative impacts 35 . Once a tooth has been traumatized, local sequelae may occur immediately or over the months or years thereafter, 6,36 leading to the requirement of years of follow‐up after a dental trauma treatment, resulting in further direct and indirect costs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic dental injuries (TDIs) are considered a public health problem due to their high prevalence 5 and physical, 6 physiological, 7 social 8 and economic consequences 7 . In addition, TDIs can have a negative impact on the quality of life of children and adolescents 9 .…”
Section: Introductionmentioning
confidence: 99%
“…During their analyses, the adolescents could not use a magnifying glass or any other tool that could modify the design. 16 The adolescents were also not allowed to return to previous images to make comparisons or alter their initial responses ,16 Questionnaire A perception survey was carried out using a questionnaire for individuals between 10 and 15 years old. 16 This instrument was composed of 12 questions (Table 1) that identified the perceptions of different dental consequences and their influence on social judgments (positive or negative).…”
Section: Image Selectionmentioning
confidence: 99%
“…15 Malocclusions, dental traumas and dental enamel disturbances may be judged negatively not just by the individual who has them, but also and even more by others. 16,17 Enamel defects have been widely discussed, mainly in terms of color and loss of structure. These defects may affect an individual's social life and self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Стоматологическое вмешательство у детей, особенно младшего возраста, является психотравмирующими фактором, который может иметь длительные негативные последствия на развивающуюся психику ребенка с неблагоприятными эффектами в отдаленные периоды его жизни [1]. Для предупреждения и уменьшения психоэмоциональной травмы ребенка стоматологические вмешательства в большинстве случаев в младшем возрасте проводятся в условиях общей анестезии или седации с использованием различных анестетиков, среди которых наиболее часто применяются ингаляционные препараты [2].…”
Section: Introductionunclassified